A new genus and three new species of fossil braconid wasps (Hymenoptera, Ichneumonoidea) from Eocene Baltic and Rovno ambers. (November 2021) - Belokobylskij, Sergey A.; Pankowski, Maximilian G.; Pankowski, Madeline V.; Zaldívar-Riverón, Alejandro
Abstract: New parasitoid wasps of the family Braconidae are documented from Eocene Baltic and Rovno ambers. A new fossil genus belonging to the braconid subfamily Exothecinae, Palaeocolastes n. gen., with its type species P . bruesi n. sp., is described and illustrated from Baltic amber. This represents the first reliable fossil record for a member of Exothecinae. Two additional new species from Baltic amber are also described: Ascogaster ( Syntaphus ) latitibialis n. sp. (Cheloninae) and Meteorus arasnitsyni n. sp. (Euphorinae). Another fossil species, Microtypus eocenus n. sp. (Microtypinae), is described from coeval Rovno amber (Ukraine), representing the first braconid species described from this deposit. A new record of a female of Diospilites brevicornis Brues, 1933 (Diospilitinae) from Baltic amber, together with variation of some diagnostic features of the species and redescription of its subfamily and genus, are also provided. UUID: http://zoobank.org/656cb1a3-b9cf-4696-ae24-0d4df9545101 .